Black Carbon Aerosol Characteristics and Its Radiative Impact over Nainital: A High-Altitude Station in the Central Himalayas - Srivastava, AK; Pant, P; Dumka, UC; Hegde, P (Journal of the Institute of Engineering, 2012)
Ground-based measurements of aerosol black carbon (BC), from a high altitude location at Nainital in the central Himalayas (during June 2006 to May 2007), were used to study its temporal variability and impact on the atmospheric radiative forcing. Diurnal variation of BC mass concentration shows single enhanced peak in the late afternoon hour. The peak is rather pronounced in winter months due to shallow and stable boundary layer condition, which is largely associated with low surface temperature. The mean BC mass concentrations were found to be as ~0.6 (±0.2), 1.4 (±0.1), 1.2 (±0.3) and 1.5 (±0.2) μg m-3 during monsoon, post-monsoon, winter and spring periods, respectively while its maximum value was ~1.8 (±0.8) μg m-3 during April. The prevailing winds revealed to facilitates the transport of BC from the distant sources to the observing site. A radiative transfer model was used in conjunction with an aerosol optical model to estimate the BC radiative forcing over the station. Results show BC forcing at the top-of-atmosphere (TOA), surface and in the atmosphere varies between about +3 to +7, -6 to -14 and +8 to +21 Wm-2, respectively which is more pronounced during spring then during monsoon depending upon BC mass loading. The positive atmosphere forcing represents a considerable amount of heating to the lower atmosphere and has been conjectured as potential factor causing global warming. The estimated heating rate of the lower atmosphere over the station was found to be ranging from 0.24 Kday-1 during monsoon to 0.58 Kday-1 during spring season. DOI: http://dx.doi.org/10.3126/jie.v8i3.5926 JIE 2011; 8(3): 1-10